Cleroda-4(18),13-dien-15,16-olide as novel xanthine oxidase inhibitors: An integrated in silico and in vitro study. - Ha Thi Nguyen (Public Library of Science (PLoS), 2021)
In the present study, in silico predictions and molecular docking were performed on five clerodane diterpenes (1-5) from Polyalthia longifolia seeds to evaluate their potential as xanthine oxidase (XO) inhibitors. The initial screening was conducted by target prediction using TargetNet web server application and only compounds 3 and 4 showed a potential interaction with XO. Compounds 3 and 4 were subsequently subjected to in silico analyses on XO protein structure (PDB: 1N5X) using Schrödinger Release 2020-3 followed by structural modeling & molecular simulation studies to confirm the initial prediction result and identify the binding mode of these compounds to the XO. Molecular docking results revealed that compounds 3 (-37.3 kcal/mol) and 4 (-32.0 kcal/mol) binds more stably to XO than the reference drug allopurinol (-27.0 kcal/mol). Interestingly, two residues Glu 802 and Thr 1010 were observed as the two main H-bond binding sites for both tested compounds and the allopurinol. The center scaffold of allopurinol was positioned by some π-π stacking with Phe 914 and Phe 1009, while that of compounds 3 and 4 were supported by many hydrophobic interactions mainly with Leu 648, Phe 649, Phe 1013, and Leu 1014. Additionally, the docking simulation predicted that the inhibitory effect of compounds 3 and 4 was mediated by creating H-bond with particularly Glu 802, which is a key amino acid for XO enzyme inhibition. Altogether, in vitro studies showed that compounds 3 and 4 had better inhibitory capacity against XO enzyme with IC50 values significantly (p < 0.001) lower than that of allopurinol. In short, the present study identified cleroda-4(18),13-dien-15,16-olide as novel potential XO inhibitors, which can be potentially used for the treatment of gout.